Simulations of Wind Energy Conversions Systems with Asymmetrically Rnsic - Pletea, Irinel Valentin; Alexa, Dimitrie; Cepareanu, Dan Dorin (Review of Industrial Engineering Letters, 2015)
The electric energy losses as well as electromagnetic pollution of the environment by the modern electric or electronic apparatus running in a commutating regime may be reduced to minimum with the help of power electronics, field which will be well developed in the next century in order to modernize industry, transport, telecommunications, etc. The paper present a wind generator system based on a new converter configuration with a asymmetrical rectifier with near sinusoidal input currents (Asim-RNSIC), we propose a method to reduce by 15%-25% of the reactive elements (capacitors and inductances) of a asymmetrical rectifiers with near sinusoidal input currents (Asim-RNSIC). This method consists of the parallel connection of two RNSIC converters of the same type, dimensioned for half of the converted nominal power and whose entry currents are phase-shifted with an angle of 30°-40° by the correct choosing of the inductances on the AC part. Thus, it results a sufficient compensation of the type 5 current harmonics generated in the power grid when the capacitors and inductances of the two rectifiers are lowered accordingly. The converter, named Asim-RNSIC, is economically and technically more competitive compared to the three-phase six-pulse full-bridge diode rectifier with passive filters.